Differences in Obesity Status on Blood Pressure at Panjang Health Center Bandar Lampung City - Putri, Syalika Dianisa; Carolia, Novita; Graharti, Risti; Oktarlina, Rasmi Zakiah; Wahyuni, Ari (CV. Jasa Sukses Abadi, 2024)
Obesity continues to be a major health problem worldwide and has become an epidemic that has worsened over the past 50 years. Obesity has a prevalence that continues to increase every year due to unhealthy lifestyles and energy intake that is greater than energy expenditure. Obesity is closely related to the habit of consuming high-fat foods, which can increase the risk of increased blood pressure. Several studies have found that a 15% increase in body weight can cause an 18% increase in blood pressure. The results of the 2018 Indonesian Basic Health Research showed that the prevalence of obesity in the Indonesian population aged 18 years and over reached 21.8%. The purpose of this study was to determine the difference in obesity status on blood pressure at the Panjang Health Center, Bandar Lampung City. This study used an observational analytical method with a cross-sectional approach. The population in this study were obese patients registered at the Panjang Health Center, Bandar Lampung City in the period August 2023 to August 2024. The total number of research subjects who met the inclusion and exclusion criteria was 113 research subjects obtained from medical records of obese patients at the Panjang Health Center, Bandar Lampung City in the period August 2023-August 2024. Data are presented in a distribution table and analyzed using the Mann-Whitney test. The results showed a P value of 0.001 which indicated that there was a difference in the effect of obesity status on blood pressure status at the Panjang Health Center, Bandar Lampung City.